PKM Pembuatan Nuget Ayam Dengan Subtitusi Sayuran Pada Kelompok Ibu-Ibu Rumah Tangga - Gawarti Gawarti; Besse Qur’ani; Rissa Megavitry (Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract.  The problem is that housewives in Panciro village lack knowledge about the importance of increasing skills and knowledge about making jam, Panciro village women do not meet standards (under quality standard), and are less serious in seeking efforts to overcome how to increase knowledge and skills in making jam. The potential of mothers to support the improvement of skills and knowledge requires training. However, knowledge and skills in making jam are still limited or less skilled due to lack of understanding or knowledge about making jam. This PKM aims to increase the knowledge and skills as well as a clear vision of the participants in the training activities so that the partner group of Panciro women is more engaged in the business of making jam as a business field that has the potential to become a creative economy industry. The methods and approaches offered in this activity are lecture, discussion, question and answer, demonstration, and training methods. The success of this program is assessed through the indicators used to measure the extent of the success of this program if the partner mothers who have been trained are able to apply the knowledge and skills independently, reaching <50% and are able to make 3 types of prototypes planned in this activity”. Based on the results of the implementation of this PKM activity, it can be concluded that the implementation of making jam for the women of Panciro Village can increase the knowledge and skills of the participants in making jam as a skill and knowledge that can provide income if done professionally as evidenced by beautiful, neat packaging. and attractive with a variety of aromas, flavors and hygiene. Keywords:  Knowledge, Skills, jam making